Ancient duplication, coevolution, and selection at the MHC class IIA and IIB genes of birds - Minias, Piotr; Edwards, Scott V.; Babik, Wiesław (Frontiers in Immunology, 2023)
The Major Histocompatibility Complex (MHC) of vertebrates is a dynamically evolving multigene family primarily responsible for recognizing non-self peptide antigens and triggering a pathogenspecific adaptive immune response. In birds, the MHC was previously thought to evolve via concerted evolution with high degree of gene homogenization and the rapid loss of orthology.However, the discovery of two ancient avian MHC-IIB gene lineages (DAB1 and DAB2) originating before the radiation of extant birds indicated that despite the action of concerted evolution, orthology may be detectable for long evolutionary periods. Here, we take advantage of rapidly accumulating digital genomic resources to search for the signal of an ancient duplication at the avian MHC-IIA genes, as well as to compare phylogenetic distribution and selection between MHC-IIA and IIB gene lineages. The analysis of MHC sequences from over 230 species representing ca. 70 bird families revealed the presence of two ancient MHC-IIA gene lineages (DAA1 and DAA2) and showed that their phylogenetic distribution matches exactly the distribution of DAB1 and DAB2 lineages, suggesting tight coevolution. The early post-duplication divergence of DAA1 and DAA2 was driven by positive selection fixing radical amino acid differences within the membrane-proximal domain and, most probably, being functionally related to the interactions between α2 and β2 chains of the MHC-II heterodimer. We detected no evidence for an overall (gene-wide) relaxation or intensification of selection at either DAA1/DAB1 or DAA2/DAB2, but codon-specific differences in selection signature were found at the peptide-binding sites between the two gene lineages, perhaps implying specialization to different pathogen regimes. Our results suggest that specific pairing of MHC-II α and β chains may have an adaptive significance, a conclusion that advances knowledge on the macroevolution of the avian MHC-II and opens exciting novel directions for future research.